TIPE family of proteins and its implications in different chronic diseases - Bordoloi, D.; Banik, K.; Shabnam, B.; Padmavathi, G.; Monisha, J.; Arfuso, Frank; Dharmarajan, Arunasalam; Mao, X.; Lim, L.; Wang, L.; Fan, L.; Hui, K.; et al. (MDPI AG, 2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. The tumor necrosis factor-a-induced protein 8-like (TIPE/TNFAIP8) family is a recently identified family of proteins that is strongly associated with the regulation of immunity and tumorigenesis. This family is comprised of four members, namely, tumor necrosis factor-a-induced protein 8 (TIPE/TNFAIP8), tumor necrosis factor-a-induced protein 8-like 1 (TIPE1/TNFAIP8L1), tumor necrosis factor-a-induced protein 8-like 2 (TIPE2/TNFAIP8L2), and tumor necrosis factor-a-induced protein 8-like 3 (TIPE3/TNFAIP8L3). Although the proteins of this family were initially described as regulators of tumorigenesis, inflammation, and cell death, they are also found to be involved in the regulation of autophagy and the transfer of lipid secondary messengers, besides contributing to immune function and homeostasis. Interestingly, despite the existence of a significant sequence homology among the four members of this family, they are involved in different biological activities and also exhibit remarkable variability of expression. Furthermore, this family of proteins is highly deregulated in different human cancers and various chronic diseases. This review summarizes the vivid role of the TIPE family of proteins and its association with various signaling cascades in diverse chronic diseases.